MAJLIS TA’LIM (ISLAMIC FORUM) AND HARMONIZING INTER FAITH COMMUNICATION - Zaenal Abidin (INJECT (Interdisciplinary Journal of Communication), 2019)
The process of growing multiculturalism and tolerance values among religious followers to the community in Indonesia can be done through religious lectures in majlis ta’lim (Islamic forum) in mosques, houses, meeting halls, etc. The lectures delivered were concerned about democracy, justice and law, cultural values and ethos, equality in differences, ethnicity, religious beliefs, cultural expressions, private and public domains, human rights, community cultural rights, and other relevant concepts. In this case, majlis ta’lim (Islamic forum) can be seen as a solution of growing the seeds of democracy, tolerance and multiculturalism for the harmonization among religious groups Indonesia. Majlis Ta’lim (Islamic forum) is a great potential since it can create a harmonious and free from radical values country, and able to reduce issues of SARA (ethnicity, religion, ancestry, and group of people), which are often raised from the institutionalization of community. Good understanding of democracy, tolerance and multiculturalism are aligned with the Islamic values.